Influences of North Pacific Ocean Domain Extent on the Western U.S. Winter Hydroclimatology in Variable‐Resolution CESM. Issue 14 (14th July 2020) - Rhoades, Alan M.; Jones, Andrew D.; O'Brien, Travis A.; O'Brien, John P.; Ullrich, Paul A.; Zarzycki, Colin M.
Abstract: Variable‐resolution global climate models (VRGCMs) are a dynamical downscaling method that can reach spatiotemporal scales needed for regional climate assessments. Over the years, several users of VRGCMs have assumed where the location and extent of the refinement domain should be based on knowledge of the prevailing storm tracks and resolution dependence of important regional climate processes (e.g., atmospheric rivers [ARs] and orographic uplift), but the effect of high‐resolution domain size and extent on the simulation of downstream hydroclimatic phenomena has not been systematically evaluated. Here, we use variable resolution in the Community Earth System Model (VR‐CESM) to perform such a test. To do this, three VR‐CESM grids were generated that span the entire, two thirds, and one third of the North Pacific and evaluated for a 30‐year climatology using Atmospheric Model Intercomparison Project protocols. Simulations are compared with reanalysis products offshore (fifth‐generation of the European Centre for Medium‐Range Weather Forecasts atmospheric reanalysis [ERA5]) and onshore (Livneh, 2015, https://doi.org/10.1038/sdata.2015.42, and Parameter‐elevation Regressions on Independent Slopes Model [PRISM]) of the western United States. The westward expansion of refinement domain influenced integrated vapor transport (IVT), which was generally high biased but minimally impacted AR characteristics. Due to slight differences in landfalling AR counts in the western United States, California winter precipitation generally improved with westward expansion of the refinement domain. Western U.S. mountain snowpack and surface temperatures were insensitive to refinement domain size and were more influenced by changes in topographic resolution and/or land surface model version. Given minimal dependence of simulated western U.S. hydroclimate on refinement domain size over the North Pacific, we advise future VR‐CESM studies to focus grid resolution on better resolving land surface heterogeneity. Key Points: Three variable‐resolution Community Earth System Model simulations are assessed for sensitivities to refinement domain size More extensive refinement of the western Pacific reduces the integrated water vapor transport bias to the western United States Topographic resolution and land surface model have greater influences on simulated hydroclimatology than refinement domain extent